Evaluating Centralisation in Healthcare Supply Chains - Andersson, Simon; Eliasson, Oliver (My University, 2026)
Healthcare supply chains face mounting pressure to deliver high-quality patient care while managing rising costs, workforce shortages, and ageing populations. Frag-mented material flows often constrain coordination, visibility, and control, and struc-tural redesigns such as centralisation are commonly considered as a response. Their effectiveness, however, depends on organisational, informational, and governance conditions that are often underdeveloped. This thesis evaluates how, and under what conditions, different forms of centralisa-tion could improve healthcare supply chain performance, taking a private healthcare provider currently considering such a redesign as the empirical case. The study com-bines expert interviews with practitioners from comparable healthcare organisations and stakeholder interviews from the case organisation. The study identifies six prerequisites for centralisation: strategic direction and management commitment, data foundations, IT infrastructure, scale and volume concentration, assortment standardisation and clinical involvement, and change-management capacity. These prerequisites interact sequentially rather than inde-pendently. The case organisation presents gaps across all dimensions, with the data foundation representing the most consequential deficiency. Its supply chain operates between the ad hoc and defined stages of maturity, with fragmented delivery flows, person-dependent ordering practices, limited central mandate, and compromised in-formation visibility forming a mutually reinforcing configuration. The findings suggest that the prior question for the case organisation is not which form of centralisation to adopt, but what preparatory work must precede the choice. Centralisation built on the current foundation is unlikely to deliver its expected benefits, as harmonisation and standardisation of the organisation must precede structural redesign. Under such conditions, centralisation is best understood not as a single structural decision but as a stage in a longer development trajectory in which organisational readiness is established before structural change is pursued.
Keywords: healthcare supply chain, healthcare logistics, supply chain maturity, sup-ply chain governance, supply chain integration, supply chain visibility, supply chain centralisation, centralisation prerequisites, supply chain configuration